Sistem Bagi Hasil pada Usahatani Padi Sawah di Desa Lalonggolosua Kecamatan Tanggetada Kabupaten Kolaka - Prihantini, Campina Illa; Mappeali, Mappeali; Hasbiadi, Hasbiadi; Berlian, Mery; Ningsih, Verry Yarda; Jafar, Rayhana; Lontoh, Rinny; Anam, Moh. Khairul (Universitas Galuh, 2025)
The sharecropping system remains a prevalent informal institution in many agricultural countries, including Indonesia. This research focuses on examining the profit-sharing practices in rice farming in Lalonggolosua Village, Tanggetada District, Kolaka Regency. Using a purposive sampling approach, 30 farmers were selected as a representative sample out of 108 rice farmers affiliated with local farming groups. Conducted between January and April 2022, the study found that the dominant sharecropping arrangement in the area involved landowners receiving one-third and tenant farmers receiving two-thirds of the yield. Income analysis revealed that tenant farmers earned an average of IDR 15.67 million per hectare per planting season, while landowner-cultivators earned slightly less, averaging IDR 15.61 million per hectare per season. The efficiency of rice farming, as measured by the R/C Ratio, averaged 4.62 and 4.72, indicating profitable operations. A t-test analysis showed no statistically significant difference in income between landowner-cultivators and tenant farmers. It is recommended that sharecropping agreements be made fairer, with clearer definitions of each party’s rights and responsibilities.